INOVASI PENGEMBANGAN LAYANAN DENTAL CENTER DAN IMUNISASI CENTER PUKESMAS. - Amirul Mustofa; Sri Roekminiati; Damajanti Sri Lestari (Jurnal Penelitian Administrasi Publik, 2020)
Public services in the health sector carried out by the puskesmas have yet to meet the most public service needs in the working area. This is since up to this study the puskesmas had not yet determined the priority scale of services. The other side is that the infrastructure and infrastructure owned are still limited. In this connection, the purpose of this study is to identify the needs of patients or the community to obtain health services that are the most common needs of the community. Furthermore, based on these data, service innovation is formulated to become the need for public health services as a form of service based on local wisdom. This research was conducted using qualitative methods, and data obtained through interviews, observations, and documents. This research results that health services in north ponorogo health center need to be changed and innovations based on local potential, so that the health center becomes a dental center service and immunization center service.